Pelatihan Pakan Alternatif Berbasis Metode Asset Based Community Development (ABCD) Sebagai Upaya Peningkatan Ekonomi Masyarakat Peternak Sapi - abdul azis, FAKIH (Dharma: Jurnal Pengabdian Masyarakat, 2025)
The Jomblang Village Farmers Group has effectively utilized a community service program to transform agricultural waste into valuable resources. By employing corn cobs, farmers have attained the capacity to independently produce high-quality fermented livestock feed. Proper training and the provision of tools have enabled the community to manage waste in a sustainable manner, thereby mitigating the adverse environmental impacts of agricultural waste. This initiative is particularly focused on addressing the challenge of limited availability of quality livestock feed during the dry season.The design and development of a tool for producing fermented feed from corn cobs was informed by observations of the partners' challenges. This tool was subsequently employed, and training was provided to the partners on the production of fermented feed and the operation of the tool. This approach empowers the partners to independently produce quality fermented feed, thereby reducing environmental pollution caused by the improper disposal of corn cobs while concurrently enhancing the quality of livestock feed